Recruitment of Labelled Monocytes by Experimental Venous Thrombi - McGuinness, C. L.; Humphries, J.; Waltham, M.; Burnand, K. G.; Collins, M.; Smith, A. (Thrombosis and Haemostasis, 2001)
Objective. Infusing monocytes that have been stimulated to produce fibrinolytic activators and factors that regulate cell proliferation, migration and maturation, might enhance venous thrombus resolution. The aim of this study was to determine the time course of infused monocyte recruitment into venous thrombus in an appropriate model of this disease. Design and Methods. Thrombus was induced in the inferior vena cava of male Wistar rats using reduced flow (80-90% stenosis). The vessel wall was examined at 1hr by scanning electron microscopy. Resolving thrombi with surrounding vena cava were obtained at 1, 7, 14 and 21 days after induction (n = 8). Sections, taken at 0.5 mm intervals (10-15 sections per thrombus), were stained using haematoxylin, Martius Scarlet Blue and antibodies against monocytes, platelets and fibrin. Sections from human venous thrombi (n = 4) were similarly stained. The area occupied by monocytes (in relative pixel units, RPU) was determined using computer aided image analysis. Peripheral rat blood monocytes were extracted, fluorescently labelled and injected intravenously into 7 rats prior to thrombus induction. Vena cava with thrombus was harvested 1 h, 2, 3, 4, 7, 14 and 25 days after induction and their fluorescence measured. The fluorescent content of the caval wall and thrombus was analysed in greater detail at 2 and 25 days after thrombus induction (n = 4 at each time interval). Results. Experimental thrombi were structurally similar to human thrombus and resolved within 14-21 days. Scanning electron microscopy showed minimal endothelial damage at 1 h with signs of early thrombus formation (platelet, red cell leukocyte and fibrin deposition). Neutrophils were the predominant leukocyte in the thrombus at 1 day, with monocytes making up only 0.3% (0.04% sem) of the area of the thrombus. There was a steady increase in thrombus monocyte content and by 21 days the percentage area of thrombus covered by monocytes had increased by over 35 fold to 11.5% (2.3% sem) (p <0.001). Initially, monocytes appeared around the edge of the thrombus and became more evenly distributed through the thrombus as resolution progressed. Labelled monocytes could be found in the circulation up to 1 week after infusion. The fluorescent content (RPU) of the thrombus increased over 25 days (mean RPU At 2 days 0.012, sem 0.005; mean RPU at 25 days 1.062, sem 0.252, p = 0.008). The number of labelled monocytes in the vessel wall peaked at 2 days and decreased thereafter.
Keywords: Venous; thrombosis; monocyte